Public Complaints Information System in Government to Improve Website-Based Public Services - Shofiana, Arista; Riadi, Aditya Akbar; Evanita, Evanita (Newinera Publisher, 2025)
Optimal public service is one indicator of the success of village government in responding to community needs. However, in Lahar Village, the public complaint process is still carried out manually, such as verbally or by hand, so it is prone to data loss, slow in handling, and less transparent. This condition indicates the need for a system that is able to digitize the complaint process to be more effective and efficient. This study aims to design and build a website-based public complaint information system to improve the quality of public services in the Lahar Village government environment. The methodology used includes direct observation, interviews with village officials, and literature studies as the basis for system design. System development is carried out using the PHP programming language and MySQL database. The expected results of this study are the creation of a computerized complaint information system that is easily accessible to the public, and supports the process of recording, handling, and monitoring complaints in a more transparent and structured manner. With this system, it is hoped that public services in Lahar Village can be significantly improved, both in terms of time efficiency and data accuracy.